Serum Levels and in vitro CX3CL1 (Fractalkine), CXCL8, and IL-10 Synthesis in Phytohemaglutinin-Stimulated and Non-stimulated Peripheral Blood Mononuclear Cells in Subjects With Schizophrenia - Arabska, Jaśmina; Wysokiński, Adam; Brzezińska-Błaszczyk, Ewa; Kozłowska, Elżbieta (Frontiers in Psychiatry, 2022)
Although schizophrenia is a severe mental illness whose etiology is still largely unknown, its pathogenesis may be associated with dysregulation of the immune mechanisms. The present study compares the levels of interleukin (IL)-10, interleukin-8 (CXCL8) and fractalkine (CX3CL1) between schizophrenic patients and healthy controls. It also assesses the ability of peripheral peripheral blood mononuclear cells (PBMCs) to produce these cytokines spontaneously and following mitogen stimulation. A prospective study was performed of 60 adult schizophrenia patients and 32 controls. CXCL8, IL-10 and fractalkine concentrations were measured in serum and supernatants from cultured PBMCs. Anthropometric (BMI, WHR) and body composition measurements were taken using bioimpedance analysis (BIA) and dual-energy X-ray absorptiometry (DXA). The schizophrenia patients demonstrated significantly higher levels of CXCL8 (schizophrenia: 13.4±15.7 pg/mL, control: 6.9±4.2 pg/mL, p = 0.001) and lower level of fractalkine (schizophrenia: 22.8±9.9 pg/mL, control: 45.4±84.5 pg/mL, p = 0.041). IL-10 levels did not significantly differ. No in vitro synthesis of fractalkine was observed. Neither unstimulated or PHA-stimulated CXCL8 secretion differed between the two groups (p >0.05). The patients not taking mood stabilisers (MS−) demonstrated significantly higher CXCL8 levels than those on mood stabilisers (MS+) (p = 0.03) and control (p <0.001). In addition, the MS− sub-group demonstrated significantly lower serum fractalkine than controls (p = 0.009). These effects could be described as pseudo-normalisation of CXCL8 and fractalkine in schizophrenia patients taking mood stabilisers.